2019
DOI: 10.26650/tjbc.20190009
|View full text |Cite
|
Sign up to set email alerts
|

Some biological characteristics, habitat requirements and implications for conservation of endemic freshwater fish Capoeta aydinensis (Turan, Küçük, Kaya, Güçlü & Bektaş, 2017) in Tersakan stream (Muğla)

Abstract: Son yıllarda endemik türlerin nesillerinin devamlılıkları ile ilgili endişeler giderek artmaktadır. Endemizm, biyoçeşitlilik mirasının devamında temel yapı taşlarından biridir. Ancak ülkemiz içsularında yer alan birçok endemik tatlısu balığı türünün temel biyo-ekolojik özellikleri ve habitat gereksinimleri üzerine bilgilerimiz oldukça kısıtlıdır. Bu bağlamda, Dalaman (Muğla)'ın Tersakan Deresi'nde bulunan Capoeta aydinensis (Turan, Küçük, Kaya, Güçlü & Bektaş, 2017) populasyonu üzerine bir yıllık bir çalışma y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The recent study reported that maximum age of C. aydinensis was 8 years; and its habitat preference is shady areas in spring, generally blurry waters in summer, high vegetation cover and blurry waters in autumn and high vegetation cover in winter (Akbaş et al, 2019). As an unusual habitat, this case report presents occurrence of an endemic fresh water fish, Capoeta aydinensis in marine waters of Gökova Bay, Aegean Sea.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The recent study reported that maximum age of C. aydinensis was 8 years; and its habitat preference is shady areas in spring, generally blurry waters in summer, high vegetation cover and blurry waters in autumn and high vegetation cover in winter (Akbaş et al, 2019). As an unusual habitat, this case report presents occurrence of an endemic fresh water fish, Capoeta aydinensis in marine waters of Gökova Bay, Aegean Sea.…”
Section: Introductionmentioning
confidence: 72%
“…In previous studies, Akbaş et al (2019) reported 364 specimens (TL range: 58-348 mm) of C. aydinensis from Tersakan Stream (Muğla) during June 2013 -June 2014. Thereafter, 150 specimens (FL range: 130-312 mm) of C. aydinensis [as C. bergamae, it had been name used before new species definition according to Akbaş et al (2019)] were captured from Topçam Dam Lake in Aydın province (Şaşı, 2009). Turan et al (2017) also reported 30 specimens (SL range: 117-179 mm) in their systematic study.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined that the abundance and distribution of this species were not correlated with the environmental variables of this wetland. Akbaş et al (2019) also showed that this endemic fish from the Tersakan Stream which flows into the Lake Koca, was a slow-growing species, therefore the age of reaching sexual maturity is higher than other fish. The destruction of habitats by anthropogenic activities and the presence of non-native fish are critical to the survival of populations of such sensitive and slow-growing species.…”
Section: Discussionmentioning
confidence: 89%
“…Although no precise data on population trends are available in the literature, the populations of this species are slowly declining due to the negative effects of anthropological activities (Yılmaz et al, 2015). Another endemic species, C. aydinensis, is a species that has a low tolerance to environmental changes and prefers specific habitats (Akbaş et al, 2019). C. aydinensis had a very low abundance and constituted 2.48% of the fish community of Lake Koca.…”
Section: Discussionmentioning
confidence: 99%